Perencanaan Sistem Otomatisasi Smartroom Berbasis Mikrokontroller Arduino Uno - Syarif Ishak Alkadri; Erick Radwitya (entries, 2023)
The development of increasingly advanced technology has now been widely applied in human life to assist in every activity. In meeting the needs of life, humans always want and think about ways to carry out daily activities effectively and efficiently. The purpose of this study was to produce a prototype for controlling electronic devices at short or long distances using a smartphone application utilizing internet connectivity which is accessed through an application installed on a smartphone. Electronic devices that can be controlled consist of 4 lights and 4 sockets. Installing this tool costs Rp. 563,000, The conclusion of this study is that you can control the on and off lights and sockets either using a switch or using the Ardiuino bluetooth controller application. control of these electronic components can be applied to residential or apartment buildings for automatic control systems and also monitoring of electronic components with the Ardiuino bluetooth controller application. Based on the results of this final project is to make a single line and wiring diagram, namely in the installation of an automatic room or smartroom, namely the use of 4 lights. .Keywords: Smartroom, Lighting Automation System, Microcontroller.